2006
DOI: 10.1111/j.1365-2929.2006.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of problem-based learning and lecturing on the development of students' critical thinking

Abstract: There were significant differences in the development of students' critical thinking dispositions between those who undertook the PBL and lecture courses, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
240
2
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(279 citation statements)
references
References 16 publications
14
240
2
23
Order By: Relevance
“…For example, study by Derry et al [16], a qualitative study result, indicated that students improved their ability to scientifically and statistically reason in problem solving in a new PBL statistical course. Similar findings were also illustrated in Tiwari et al [7], one year long of PBL treatment enhanced students' critical thinking ability, compared to conventional approach. Also, in Iwaoka et al [17], students in Food Science and Human Nutrition Course indicated a significant increase in their critical thinking in several years of comparison of conventional approach.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…For example, study by Derry et al [16], a qualitative study result, indicated that students improved their ability to scientifically and statistically reason in problem solving in a new PBL statistical course. Similar findings were also illustrated in Tiwari et al [7], one year long of PBL treatment enhanced students' critical thinking ability, compared to conventional approach. Also, in Iwaoka et al [17], students in Food Science and Human Nutrition Course indicated a significant increase in their critical thinking in several years of comparison of conventional approach.…”
Section: Introductionsupporting
confidence: 74%
“…This method is generally agreed to have important implications for transfer of knowledge and application of problem solving skills to novel situations [6]. This assertion has been supported by several previous research reports [7][8][9].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results showed that the significant difference in the development of critical thinking amongst the students from the PBL course occurred as a result of the encouragement of students' active participation in small-group discussions. In a PBL programme, students registered significantly higher critical thinking disposition scores on completion of their training and this remained for two years afterwards although to a lesser degree [19] . The didactic content format tends to limit discussion, the use of logic, problem solving and creativity amongst students.…”
Section: Discussionmentioning
confidence: 99%
“…Es posible, en este sentido, caracterizar al pensamiento crítico como proceso de conflicto cognitivo, al considerarlo como habilidad que permite cuestionar y evaluar, lo que supone problematizar el conocimiento que se tiene con la finalidad de mejorarlo y tomar decisiones adecuadas (Bouzas, 2009;Olivares & Heredia, 2012); esto se ha relacionado con el aprendizaje basado en problemas, permitiendo además el fortalecer el trabajo cooperativo. El desarrollo de actividades de resolución de problemas es un método que permite el fomento de pensamiento crítico en estudiantes universitarios (Sánchez, 2012;Tiwari, Lai, So, & Yuen, 2006), esto dado que implicaría asumir un esfuerzo de cambio de esquemas cognitivos, para establecer conexiones y evaluar los pasos realizados, así como para generar conclusiones razonadas y reflexivas.…”
Section: Proceso Complejo Y Dinámicounclassified